Effect of Compressed Gas on Deep Mine Long-Distance Backfill Pipe Flushing: From Laboratory to Industrial Tests - Longjian Bai; Hongjiang Wang; Aixiang Wu; Hao Li; Shengkai Wang; Chong Chen; Chunkang Liu (Advances in Civil Engineering)
The clean filling pipe can ensure sufficient overflow section, reduce paste transport resistance, and avoid slurry deposition. The introduction of compressed gas into the pipe flushing can improve the flushing effect and efficiency of the pipe and reduce water consumption. However, the dominant factors influencing water consumption water consumption are not well understood. The purpose of this study is to determine the effect of flow velocity, backfill gradient (4–7), gas void fraction (0–1), and gas pressure (0–0.7 MPa) on water consumption. Water consumption was obtained experimentally by modeling the gas–water flushing pipe. The criterion for the completion of pipeline cleaning is to reduce the water solid content of the flushing pipeline from the initial value to 1%. A model was established to predict water consumption, which was validated by industrial tests. The results show that the water consumption of the flushing pipe increased with the power law as the backfill gradient increased and decreased with the increase of gas void fraction, gas pressure, and flow velocity. The water consumption is 0.8–1.1 times the volume of the pipe in water flushing. However, the water consumption of gas–water flushing is 0.60–0.75 times the volume of the pipe. Gas–water flushing can reduce water consumption by up to 30%. The findings are conducive to design pipe flushing parameters to avoid excessive water consumption.